دور العدالة التنظيمية في تعزيز سلوك المواطنة التنظيمية في المؤسسة الاقتصادية.دراسة ميدانية بالمديرية العملية للإتصالات الجزائر بالوادي - غادة, أحمودة; إيمان, غندير; الطيب, قديري (University of eloued جامعة الوادي, 2020)
"تهدف الدراسة إلى إبراز دور العدالة التنظيمية بأبعادها (العدالة التوزيعية، العدالة الإجرائية، العدالة التعاملية ) في تعزيز سلوك المواطنة التنظيمية بأبعادها ( الإيثار، الكياسة، الروح الرياضية، وعي الضمير، السلوك الحضري ) لدى مؤسسة اتصالات الجزائر لولاية الوادي، و اعتمدنا لذلك على منهج الوصفي التحليلي لإبراز المفاهيم المتعلقة بموضوع البحث، و تحليلها و استقراء النتائج. ولتحقيق أهداف الدراسة تم تصميم الاستبيان الذي شمل ......... لجمع المعلومات الأولية حيث تم معالجة 114 إستمارة استبيان بواسطة البرنامج الإحصائي SPSS-V.25وذلك باستخدام العديد من الأساليب الإحصائية منها:المتوسطات الحسابية و معامل الارتباط و الانحدار خطي البسيط،واختبارT ومن أهم النتائج التي توصلنا لها دراسة هناك علاقة ذو دلالة احصائية بين العدالة التنظيمية و سلوك المواكنة التنظيمية عند مستوى المعنوية5%في مؤسسة اتصالات الجزائر بالوادي. *لا يوجد دور الشعور بالعدالة التوزيعية في تشكل سلوك المواطنة التنظيمية لدى موظفي المؤسسة بإتصالات الجزائر بالوادي عند مستوى المعنويه 5%. *يوجد دور الشعور بالعدالة الإجرائية في تشكل سلوك المواطنة التنظيمية لدى موظفي المؤسسة باتصالات الجزائر بالوادي عند مستوى معنويه10٪ * يوجد دور الشعور بالعدالة التعاملية في تشكل سلوك المواطنة التنظيمية لدى موظفي مؤسسة اتصالات الجزائر عند مستوى معنوية 99% "" The study aims to highlight the role of organizational justice in its dimensions (distributive justice, procedural justice, transactional justice) in promoting organizational citizenship behavior in its dimensions (altruism, civility, sportsmanship, conscience awareness, urban behavior) at the Algeria Telecom Corporation for the state of the valley, and we relied for that on the approach Descriptive-analytical to highlight the concepts related to the topic of research, and to analyze and extrapolate the results. To achieve the objectives of the study, a questionnaire was designed that included ......... to collect primary information, as 114 questionnaire forms were processed by the statistical program SPSS-V.25, using many statistical methods, including: arithmetic averages, correlation coefficient and simple linear regression. And the T-test, and one of the most important results that we reached for a study, there is a statistically significant relationship between organizational justice and the behavior of organizational empowerment at the level of morale at 5% in Algeria Telecom in the valley. * There is no role in the sense of distributive justice in the formation of organizational citizenship behavior among the employees of the institution in Algeria Telecom in the valley when the morale is 5%. * There is a role of a sense of procedural justice in the formation of organizational citizenship behavior among the employees of the institution in Algeria Telecom in the Valley at the level of morale10% * There is a role of a sense of transactional justice in the formation of organizational citizenship behavior among the employees of Algeria Telecom at a morale level of 99% Keywords: organizational justice, organizational citizenship behavior. "
مذكرة ماستر ادارة اعمال
Keywords: العدالة التنظيمية. سلوك المواطنة التنظيمية; organizational justice. organizational citizenship behavior